E-Commerce System For Pharmaceutical Products - Tan, Yeong Hean (2001)

(untitled)
The purpose of this project is to develop a prototype e-pharma catalog application for pharmaceutical products in Malaysia. The e-pharma website provides on-line ordering pharmaceutical products services to customers. Other services include on-line counselling from recognize pharmacists, information about drugs and health care, addresses of health centres throughout Malaysia, pharmaceutical education etc. Besides that, there are health calculators such as Body Mass Index (BMI) calculator, calories calculator etc. There are four main functional modules in the e-pharma business model. They are view information module, on-line ordering module, advertising module and pharmacists consulting module. This project uses the Web Page Development Methodology (WPD) as the development methodology. Finally, this project discusses some flaws, constraints and recommendations for the future development.